2016
DOI: 10.1080/01494929.2016.1157559
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Help-Seeking: A Review of the Efficacy and Reach

Abstract: Formal and informal relationship help-seeking is becoming increasingly common. This article discusses seven forms of relationship help-seeking: couple therapy, couple relationship education, self-help books, internet resources, other media sources, talking with clergy, and talking with friends and family. The purpose of this literature review is to organize the relationship help-seeking research, bring to light some of the less accessible research, and offer recommendations to researchers and practitioners reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 80 publications
(82 reference statements)
0
29
0
1
Order By: Relevance
“…In stand‐alone and automated designs, there is variability in the delivery method (e.g., website vs. smart phone app) and extent of personalization or complexity of feedback (Muñoz et al, ). For example, self‐guided relationship education websites such as http://twoofus.org and http://coupleconnection.net provide couples with information and advice on commonly reported relationship issues without any personalized content (Stewart, Bradford, Higginbotham, & Skogrand, ). Furthermore, a text‐based program, Love Every Day, funded by the Department of Defense via Military OneSource, prompts couples once daily for 21 days to answer questions about their relationship to promote emotional closeness (U.S. Department of Defense, ).…”
Section: Role Of Coach Support In Web‐based Interventionsmentioning
confidence: 99%
“…In stand‐alone and automated designs, there is variability in the delivery method (e.g., website vs. smart phone app) and extent of personalization or complexity of feedback (Muñoz et al, ). For example, self‐guided relationship education websites such as http://twoofus.org and http://coupleconnection.net provide couples with information and advice on commonly reported relationship issues without any personalized content (Stewart, Bradford, Higginbotham, & Skogrand, ). Furthermore, a text‐based program, Love Every Day, funded by the Department of Defense via Military OneSource, prompts couples once daily for 21 days to answer questions about their relationship to promote emotional closeness (U.S. Department of Defense, ).…”
Section: Role Of Coach Support In Web‐based Interventionsmentioning
confidence: 99%
“…The level of desire to seek services may also vary by individual factors and types of presenting problems. First, several studies have found significant gender differences such that women are more likely to seek couple therapy compared to their male partners (Doss, Atkins, & Christensen, 2003;Stewart, Bradford, Higginbotham, & Skogrand, 2016). In addition, there is mixed evidence for the possibility that types of presenting problems partners endorse differ by gender.…”
Section: Reasons For Seeking Couple Therapymentioning
confidence: 99%
“…For example, couple relationship problems are reported as the most common presenting concern among those seeking assistance from professional counsellors (Kulka, Veroff, & Douvan, 1979), and one of the top three presenting problems in those attending Employee Assistance Programs (Shumway, Wampler, Dersch, & Arredondo, 2004). The pervasiveness of relationship help-seeking is reflected in the millions of websites and thousands of self-help books that are used by millions of people (Stewart, Bradford, Higginbotham, & Skogrand, 2016).…”
Section: Significance Of Couple Relationships and Couple Therapymentioning
confidence: 99%
“…It is likely that many more people would like professional help with their relationship problems, except that clients often perceive a lack of expertise among helping professionals about relationship issues (Stewart et al, 2016). Individuals in distressed relationships are greatly overrepresented among those seeking mental health services, yet they usually do not report marital distress as a primary complaint (Lin, Goering, Offord, Campbell, & Boyle, 1996), possibly because they do not perceive mental health professionals as able to address relationship issues.…”
Section: Significance Of Couple Relationships and Couple Therapymentioning
confidence: 99%